Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan : (Studi pada salah satu perusahaan penjaminan kredit di Kota Bandung) - Eko Prasetiyo; Farid Riadi; Nenny Rinawati; Retno Resawati (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
Individual motivation in the organization is a significant contribution to improving employee performance and work discipline, where the more disciplined employees are, the better their performance will be. This study aims to determine the effect of motivation and work discipline on employee performance. The research method used is a survey research method with a sample of employees who work at a credit guarantee company in Bandung. The sample in this study was 40 employees. Researchers use path analysis techniques to answer the problem formulation that has been set previously. The results showed a significant effect of motivation and work discipline on employee performance. The study results recommend that the company further improve employee motivation and work discipline to achieve optimally.